Corneal epithelial dendritic cells, tear neuropeptides and corneal nerves continue to be affected more than 12 months after LASIK. Issue 3 (17th October 2022) - Chao, Cecilia; Tajbakhsh, Zahra; Stapleton, Fiona; Mobeen, Rabia; Madigan, Michele C.; Jalbert, Isabelle; Briggs, Nancy; Golebiowski, Blanka
Abstract: Purpose: LASIK causes corneal nerve damage and may affect the neuro‐immune crosstalk. This study examined the effects of LASIK on corneal epithelial dendritic cells (CEDC) density and morphology and explored their relationships with corneal nerves and tear neuropeptides. A grading system was developed to assess CEDC morphology. Methods: Intra‐ and inter‐observer repeatability of the CEDC morphology grading system was established using kappa (κ). In vivo confocal microscope images of the central cornea were captured from 20 participants who had undergone LASIK 12–16 months earlier and 20 controls (age 18–32 years, 55%F). CEDC density was counted manually, and CEDC morphology was assessed using a new grading system. CEDC sub‐types (contacting nerves [CEDCc] and not contacting nerves [CEDCnc]) were also assessed. Differences in CEDC density and morphology were examined using mixed models and chi‐squared test. Relationships between CEDC and corneal nerve parameters and tear substance P were explored using Spearman's correlation. Results: Excellent intra‐ and inter‐observer repeatability was demonstrated for the grading system (κ = 0.82–0.97). In post‐LASIK participants, CEDC density was lower compared with controls (5 [0–34] vs. 21 [7–77] cells/mm 2 ; p  = 0.01), and the proportion of CEDC with thick dendrites was higher (55%–73% vs. 11%–21%, p  < 0.003). Higher tear substance P levels were associated with higher CEDC density (rho = 0.48, p  = 0.003). Fewer nerve interconnections were observed in participants in whom CEDC had dendrites ( p  = 0.03). CEDC sub‐types followed a similar pattern to CEDC. Conclusions: The findings suggest that CEDC may remain altered more than 12 months post‐LASIK. The association with substance P suggests a role for CEDC in corneal neurogenic inflammation.